Horizontal Transfer of the “Popcorn-Effect” Strain of Wolbachia from Drosophila melanogaster to Stomoxys calcitrans - ENDANG SRIMURNI KUSMINTARSIH (Indonesian Society for microbiology, 2009)
The Wolbachia containing haemolymph from Wolbachia infected Drosophila third/fourth instar larvae was transferred through microinjection into 5-days-old pupae of the blood sucking stable fly, Stomoxys calcitrans. There was no previous record of Wolbachia being present in S. calcitrans. From a total of 682 emerging adults, 236 were females and of these, seven females were tested positive (approximately 3%) for Wolbachia infection. Using electron microscopy, it was shown that Wolbachia were present in the muscle tissues of S. calcitrans.